Thoughts on the Decriminalisation of the Use or Possession of Cannabis Within Private Settings – Minister of Justice and Constitutional Development v Prince 2019 (1) SACR 14 (CC) - Philip Stevens (Obiter, 2021)
The use or possession of drugs has been a phenomenon since time immemorial. In South Africa, the essential offences pertaining to drugs are provided for in the Drugs and Drug Trafficking Act 140 of 1992 (the Act). The two most important crimes provided for in the Act are “dealing in drugs” and the “use or possession of drugs”. The Act divides drugs into three general categories – namely, dependence-producing substances; dangerous dependence-producing substances; and undesirable dependence-producing substances. The specific drugs resorting in each of these categories are listed in Schedule 2 of the Act. The punishment prescribed for the possession, use or dealing in dangerous dependence-producing substances and undesirable dependence-producing substances is harsher than that for possession, use or dealing in dependence-producing substances. It is interesting, and topical for purposes of the current discussion, that cannabis or dagga is classified in terms of Schedule 2 as an undesirable dependence-producing substance.The case under discussion (Minister of Justice and Constitutional Development v Prince 2019 (1) SACR 14 (CC)) is of particular importance as the use or possession of cannabis within private settings was addressed from a constitutional perspective and, more pertinently, on a question as to the constitutionality of the criminalisation thereof. Upon first glance, it seems as though the issues addressed in this case correspond with the disputes addressed in the earlier case of Prince v The President, Cape Law Society (2002 (2) SA 794 (CC) (Prince (2)). As is indicated in this contribution, the issues in these two judgments are distinct and differ in many instances.A critical analysis of the decision under discussion reveals that although the use or possession of cannabis within private settings has, by virtue of the case, been decriminalised against a constitutional backdrop, it also opens the door to critical debate pertaining to various substantive and procedural issues.